Pembuatan Lengan CNC Router Gantry 350x170x12 mm Komposit Epoxy-Pipa Aluminium, Kapasitas 0,19 Unit/Jam - Firman Yasa Utama; Syamsul Hadi; Fabio Canavaro Brian Irawan; Eky Sukma Nurillah; Mochammad Alfin Ardian Syah; Ali Hasbi Ramadani; Nur Aini Susanti (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
The heavy weight of the 3-axis router gantry arm and the high cost of manufacturing are the problems faced. The purpose of manufacturing is to obtain low weight and manufacturing costs. The method of manufacturing the router gantry arm includes: design of the arm with a width of 350, a height of 170 mm, a thickness of 12 mm; making a composite mold of the gantry arm measuring 350 × 170 × 12 mm from wood; preparation of 5 pieces of Aluminum pipes as reinforcement with a diameter of 6 mm, a length of 120 mm and 140 mm which are bent to the side in the router shaft section; composite molding with epoxy resin and aluminum pipe reinforcement arranged parallel with a distance of 30 mm from each other in an upright position, except for the position where the hole is bent to the side; making a Router shaft hole with a diameter of 20 mm and other binding holes with a diameter of 10 mm and 6 mm; and quality and dimension inspection. The manufacturing results are a router gantry arm with a width of 350, a height of 170 mm, a thickness of 12 mm with a weight of about 680 g or 44.90% lighter than solid aluminum material; The total manufacturing cost is IDR 108.125/unit, and the production process duration is 310 minutes/unit, which implies that the weight of the pole arm is reduced to around 55% compared to solid aluminum material and the price is cheaper by one-third.